KARAKTERISTIK WILAYAH, DEMOGRAFI, DAN MOTIVASI PEMELIHARAAN AYAM RAS PETELUR DI KABUPATEN KONAWE SELATAN, SULAWESI TENGGARA - Rahadi, Syam; Tyasari, Irma; Sarwoko, Endi; Rusno, Rusno (Jurnal Peternakan (Jurnal of Animal Science), 2023)
The business of laying hens in Konawe Regency, Southeast Sulawesi, has a very large opportunity, an area that is known as an agriculture-based area as well as a food support area for Kendari City as the provincial capital. This study aims to examine regional characteristics, demography of laying hen breeders, and motivation to raise livestock. This research is a qualitative research with a descriptive aim to describe certain conditions or phenomena. Information selection was carried out by purposive sampling, required to have experience in raising laying hens for 2 years and snowball sampling. Data collection was carried out by direct interviews and observations at plantation business locations. During the Covid-19 Pandemic visits to informants carried out strict health protocols. Some additional information for matters deemed important is confirmed and re-validated by telephone. The topography of the land in Konawe Selatan Regency generally has an undulating and hilly land surface. The height of the land above sea level ranges from 0-1000 meters, dominantly at an altitude of 100-500 meters which reaches 39%, with a land slope between 0-36 degrees, the soil type is dominated by grumosol, podzolic and latosol, between these hills, land stretches which are potential areas for the development of the agricultural and livestock sectors. The distribution of land use in South Konawe Regency is as much as 24% (1008.21 km2) which has the potential to be used as agricultural land and livestock. The average temperature, humidity, wind speed, air pressure, and solar radiation in South Konawe Regency throughout 2020 are as follows 26.79°C, 85.25%, 1 m/s, 1009.57 mb, and 47.33%. The main business of laying hens is 76.92% as breeders, the average age of breeders is 49.00 ± 16.65 years with farming experience of 7.49 ± 7.41 years. The education of breeders was dominated by high school graduates (46.15%) and university graduates (38.46%). In general, the motivation to raise laying hens is 92.31% as the main business and 7.69% as a side business.